2009
DOI: 10.1386/jdsp.1.2.177_1
|View full text |Cite
|
Sign up to set email alerts
|

The somatic practice of intentional rest in dance education preliminary steps towards a method of study

Abstract: Every performing art has its caesura -a resting pause -a potent stillness in the rhythmic flow of action. For western contemporary dance, stillness is a powerful aesthetic tool. Far less understood are the physiological -and behaviouralbenefits of rest. While rest intervals routinely are prescribed in sports science to promote physiological recovery and improve performance, such protocols are unknown in dance. Somatic approaches ('somatics') purposely embed intervals of stillness and rest for active listening … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…The article by Batson (2009) explores the values of "intentional rest" within the context of dance education and training. Specifically, Batson reviews the existing literature on the intersections of somatic technique and modern dance, then uses that information to analyze the writings of Master's degree dance students who have taken her six-week seminar on somatics.…”
Section: The Case For Somatic Practicementioning
confidence: 99%
See 2 more Smart Citations
“…The article by Batson (2009) explores the values of "intentional rest" within the context of dance education and training. Specifically, Batson reviews the existing literature on the intersections of somatic technique and modern dance, then uses that information to analyze the writings of Master's degree dance students who have taken her six-week seminar on somatics.…”
Section: The Case For Somatic Practicementioning
confidence: 99%
“…Specifically, Batson reviews the existing literature on the intersections of somatic technique and modern dance, then uses that information to analyze the writings of Master's degree dance students who have taken her six-week seminar on somatics. Key to Batson's (2009) writing is the idea that rest, while part of every somatic practice and ingrained into most all human activities, has not been adopted by the dance world. By pushing their bodies to the limit through repetitive practice, dancers who train at a high level make themselves susceptible to overuse injuries.…”
Section: The Case For Somatic Practicementioning
confidence: 99%
See 1 more Smart Citation
“…The findings of this study provide support for the application of a sports-based model of overtraining risks and outcomes within a dance-specific context and highlight the need for greater understanding of recovery-stress balance in dance training environments. Recovery has not been widely studied in dance research and despite the identified need for a better understanding of rest and recovery in dance (Batson 2009), this area of research is still in its infancy. Thus, the possibilities for future research abound.…”
Section: Future Researchmentioning
confidence: 99%
“…361 Glenna Batson (2009), "The somatic practice of intentional rest in dance education -preliminary steps towards a method of study", Journal of Dance and Somatic Practices Vol. 1 Nο.…”
Section: η ανάπτυξη σωματικών έξεων στους επαγγελματίες χορευτές και χορεύτριες μπαλέτουmentioning
confidence: 99%